Impact of atrazine on the dynamic response of Daphnia pulex populations to fish predation risk - Qin, Shanshan; Xia, Tian; Li, Gongzheng; Gu, Lei; Sun, Yunfei; Yang, Zhou (Frontiers in Ecology and Evolution, 2023)
Herbicide pollution is persistent, which not only has a negative impact on individual organisms, but also may alter population dynamics and stability of interspecific relationships. Cladocerans, an important part of zooplankton, are often simultaneously exposed to environmental pollutants and predation risk in the aquatic environment. To evaluate the combined effects of atrazine and fish predation risk on the population traits of cladocerans, we exposed Daphnia pulex to different concentrations of atrazine (0, 0.05, 0.10, and 1.0 mg L−1) with or without fish (Rhodeus ocellatus) kairomone, recorded the key population traits, and fitted Gaussian model to population dynamics. Results showed that fish kairomone increased the population density at the end of the experiment and resting eggs production, and tended to decrease the total biomass and the average dry weight per individual of D. pulex. Atrazine reduced the total biomass, the average dry weight per individual, and resting eggs production of D. pulex populations. Atrazine also decreased the population density at the end of the experiment of D. pulex in fish kairomone treatment, and attenuated the promoting effect of fish kairomone on resting eggs production and the reduction of the total biomass. The findings highlighted the importance of considering the combined impact of environmental pollutants and predation risks on zooplankton populations.